Osteoid Metaplasia in Femoral Artery Plaques Is Associated With the Clinical Severity of Lower Extremity Artery Disease in Men - Laivuori, Mirjami; Tolva, Johanna; Lokki, A. Inkeri; Linder, Nina; Lundin, Johan; Paakkanen, Riitta; Albäck, Anders; Venermo, Maarit; Mäyränpää, Mikko I.; Lokki, Marja-Liisa; Sinisalo, Juha (Frontiers in Cardiovascular Medicine, 2020)
Lamellar metaplastic bone, osteoid metaplasia (OM), is found in atherosclerotic plaques, especially in femoral arteries. In carotid arteries OM has been documented to be associated with plaque stability. This study investigated the clinical impact of OM load in femoral artery plaques of patients with lower extremity artery disease (LEAD) using a deep learning based image analysis algorithm. Plaques from 90 patients undergoing endarterectomy of the common femoral artery were collected and analyzed. After decalcification and fixation, 4µm thick longitudinal sections were stained with Hematoxylin and Eosin, digitized and uploaded as whole slide images on a cloud-based platform. A deep learning - based image analysis algorithm was trained to analyze the area percentage of OM in whole-slide images. Clinical data was extracted from electronic patient records and the association with OM was analyzed. Fifty-one (56.7%) sections had OM. Females with diabetes had a higher area percentage of OM than females without diabetes. In male patients, the area percentage of OM inversely correlated with toe pressure and was significantly associated with symptoms. According to our results OM is a typical feature of femoral artery plaques. The OM load in the plaques was associated with diabetes in females and severity of LEAD in males. There is a difference in the association of OM load with clinical features of LEAD between male and female patients highlighting the need for a gender specific approach in the study of the mechanisms of atherosclerotic disease. In addition, the role of plaque characteristics in the treatment of atherosclerotic lesions warrants further consideration in the future.